Public trust and state management of the COVID-19 pandemic in Nigeria - Abayomi, Kolapo Quadri (Frontiers in Political Science, 2024)
The COVID-19 pandemic generated generated an unprecedented global crises with long-lasting consequences. In this study, I examine the bi-directional nexus between public trust and the management of the pandemic in Nigeria. I argue that there is a relationship vicious cycle between government management of public policies and the level of public trust. The research draws upon on the Theory of Trust, and in-depth interviews (IDI), focus group discussions (FGD), and qualitative research methods involving In-depth Interviews (IDI) and Focused Group Discussion (FGD), supported by other authoritative secondary sources. I fouind that the main reason for citizens' resistance to major policies introduced by the government to contain the spread of the pandemic was due to an entrenched lack of trust in the government, its agencies and officials. The findings also indicate that a lack of transparency and accountability in the management of the pandemic deepened the already fractured public trust. This was particularly visible in the shrouded pattern of disbursing cash transfers, allegations of corruption against the managers of the pandemic, and evidence of hiddenconcealed palliatives meant to cushion the negative economic effects of measures introduced at the peak of the pandemic to contain the spread. The paper recommends that the Ggovernment needs to promote public trust through by being responsive and responsible to public concernsadopting an open governance approach that institutionalises transparency and accountability, foster constant and consistent citizen engagement on government policies and programmes, institutionalising transparency and accountability in the activities of the government, strengthening critical agencies, and engendering a sense of belonging for all citizens.